The Adoption of Green Technologies in Indonesia : Shrimp Farmers' Facebook Group as an Online Community of Practice - Pratiwi, Ayu; Lee, Guenwoo; Farikhah; Kettunen, Erja (Wiley, 2025)
This study contributes to literature on learning pathways and agricultural innovation diffusion by exploring the use of a virtual platform on the adoption of green technologies in a global South context. The case depicts online learning within a significant food system in Southeast Asia, Indonesian shrimp farming, and focuses on the dissemination of innovation within an online group. Based on a data set of 1059 shrimp farmers, we investigate the effects of membership in the Indonesian Vannamei Shrimp Communities (KUVI), a prominent Online Community of Practice (OCoP) on Facebook. We compare the adoption of green technologies between KUVI members and non-members, and focus on how learning takes place in KUVI and how it influences technology adoption by shrimp farmers engaged in traditional extensive farming characterized by low stock density and minimal infrastructure, and those involved in more advanced intensive farming with higher stock densities and more advanced infrastructure. We find that KUVI members expanded their information sources on shrimp cultivation and significantly gained new information compared to non-members, leading to the adoption of green technologies that address a major farming issue namely the prevention of shrimp disease. Since information in KUVI is codified rather than tacit, we also find differences between the two types of farming: KUVI members in extensive farming adopted context-dependent technologies to cope with climate issues, while intensive farmers' environmentally friendly practices were more precise and strongly related to shrimp quality and productivity. The results indicate that not all agricultural information can be effectively disseminated using virtual platforms, as users have different cognitive capacities to absorb the information. Thus some practices still require experience and tacit knowledge from physical peers to be properly implemented.